Subak from the Perspective of Collaborative Governance in Realizing Heritage Tourism in Bali - Ni Putu Ayu Yudanti; Nyoman Diah Utari Dewi (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
The management of Subak as a heritage tourism destination in Bali requires a governance model capable of balancing cultural heritage preservation with sustainable tourism development. This study aims to analyze the coordination patterns among stakeholders in managing Subak as a heritage tourism destination through the perspective of Collaborative Governance. A descriptive qualitative approach was employed using document analysis of laws and regulations, government policy documents, UNESCO publications, Subak awig-awig (customary regulations), and relevant previous studies. The findings reveal that Subak management involves four primary stakeholders: the government, indigenous communities (krama Subak), the private sector, and local communities, each with interconnected roles and interests. The collaborative process is built upon five key dimensions, namely participation, legitimacy, trust, accountability, and shared understanding, which collectively support effective governance. The implementation of collaborative governance contributes to community empowerment through tourism-based economic activities, the preservation of Subak culture through the strengthening of awig-awig and the revitalization of traditional practices, and local economic development through the diversification of community income sources. However, power imbalances between krama Subak, government institutions, and private investors remain a significant challenge, potentially limiting the substantive participation of indigenous communities in decision-making processes. Therefore, strengthening collaborative governance mechanisms grounded in the values of Tri Hita Karana is essential to ensure the long-term sustainability of Subak's ecological, cultural, social, and economic functions while preserving its status as a UNESCO World Cultural Heritage site.